A Critical Examination of Zambia's Democratic Performance since 1991 - Banda, Mabvuto (Department of Political Studies, 2022)
A qualitative research approach and the reliance to a large extent on existing literature are used in this study to demonstrate Zambia's stagnant position in becoming a true democracy. While the country is seen as a beacon of peace in Africa, reflected in the peaceful transfer of power after elections, police brutality is rampant. Those with divergent views are not spared and suffer at the hands of police using the Public Order Act in instances of ‘breach of peace' and as an excuse for maintaining ‘public order'. Zambia continues to have a poor human rights record, reflected in the perpetration of violence against its citizenry with impunity by government officials and the political elites. Alleged cases of corruption rarely end in convictions despite overwhelming evidence of illegal practices. The Electoral Commission of Zambia and the judiciary are often accused of being biased towards the political establishment. A failure to appear autonomous has not only negatively affected their operations but has created negative perceptions and a loss of public confidence in these critical institutions. This, in turn, has resulted in the further undermining of democracy, as these important agencies are seemingly ineffective in ensuring that Zambia becomes a true democracy.